No foresight, no food? Regional scenarios for Africa and South Asia - Vervoort, Joost M.; Ericksen, Polly J. (Global Forum on Agricultural Research, 2012)
What would be the impacts of this kind of future on food security for the region s poor, who live under pressures of climate change? What new challenges would emerge? Could tensions arise from East Africa s assertion of power? What about a future where political and economic fragmentation continues in East Africa and people in power only focus on gains for their own narrow interests? Would there be a backlash and public outcries for change? How will these futures affect adaptation to climate change in the region? Will natural environments bear the burden either of development or exploitation in both future scenarios? Most importantly how would organizations and individuals in the region who aim to improve food security, environments and rural livelihoods navigate these futures?